The Role of Social Media in Digital Entrepreneurship Growth : Trends and Future Directions - Irwan Adimas Ganda Saputra; Lifa Farida Panduwinata; Susanti Susanti; Siti Sri Wulandari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In today’s era, social media has become a driving force for increasing digital entrepreneurship. Businesses are utilizing social media sites such as Instagram, TikTok, LinkedIn, or even Facebook to brand their companies or products and interact with clients. This is great news for businesses, especially SMEs, to have low-cost access to key markets worldwide. One evident trend is the emergence of social commerce – business-to-consumer commerce without intermediaries, exclusive of other e-commerce models. However, the adoption of social media in digital entrepreneurship comes with several challenges, such as changes in algorithms that can affect content visibility and risks related to data security and user privacy. Nevertheless, social media remains useful in terms of analytics to support strategic decisions. This study shows the value of social media for entrepreneurship and technologies that help improve content personalization and consumer behavior analysis, such as artificial intelligence and big data. This study attempts to fill the gap in the literature by looking at the differences in the outcomes of social media use in developing and developed countries and the outcomes of new technologies on digital business ventures.